Sosialisasi Perbankan Syariah pada Murid SMA Ethika Palembang - Fadilla Fadilla; Muharir Muharir (AKM, 2020)
The existence of Sharia Banking today shows a rapid development, this is evident from the number of Islamic banks in Indonesia such as Mandiri Islamic banks, BNI Syariah, Bank Babel Syariah and others. In addition to the development of existing Banking this growth can also be seen from many institutions of development of Islamic tertiary institutions that open Sharia Banking study programs, in Palembang PTKIN who opened a Sharia Banking study program was UIN Raden Fatah while its PTKIS STEBIS (School of Economics and Sharia Business) IGM. Although it is well-known and growing, there are still many who do not know about Sharia Banking and its educational institutions, therefore we as lecturers from STEBIS IGM conducts socialization on Sharia Banking to Arinda Palembang High School students. This socialization was carried out on 17 and 19 February 2020 at Arinda High School. From the results of the questionnaire about the knowledge or mastery of the material conveyed, it is known that as many as 81% of the participants of the socialization understand the Definition of Sharia Banking. As many as 70% of the participants of the socialization understand the Differences of Islamic Banking & Conventional, 74% of the participants of the socialization understand Sharia Banking Products. As many as 92% of the participants of the outreach knew the acronym STEBIS IGM. Seventy-seven percent (77%) of participants knew about the campus that opened the Islamic Banking department. As many as 81% of the socialization participants understood the legal basis of Islamic banking and 74% of the participants knew about Islamic banks in Palembang.